Asymmetric expectation effects of regime shifts and the great moderation - Zheng Liu; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2007)
The possibility of regime shifts in monetary policy can have important effects on rational agents' expectation formation and equilibrium dynamics. In a dynamic stochastic general equilibrium model where the monetary policy rule switches between a dovish regime that accommodates inflation and a hawkish regime that stabilizes inflation, the expectation effect is asymmetric across regimes. Such an asymmetric effect makes it difficult but still possible to generate substantial reductions in the volatilities of inflation and output as the monetary policy switches from the dovish regime to the hawkish one.
Keywords: E32; E42; E52; 330; structural breaks; expectations formation; monetary policy regime; macroeconomic volatility; Lucas critique; Inflationserwartung; Geldpolitik; Dynamisches Gleichgewicht; Theorie